2019
DOI: 10.1080/01426397.2019.1677881
|View full text |Cite
|
Sign up to set email alerts
|

Visitors’ preferences for landscape conservation in Alpine environments:Differences across regions, conservation programmes, and socio-economic groups

Abstract: In many regions, the scenic beauty of landscapes, and a high degree of 'naturalness', are paramount for tourism. The focus of the paper is on empirical estimates of the benefits of nature conservation programs in regard to different degrees of naturalness in two regions in the Austrian Alps. The results of an on-site survey indicate that most respondents would accept stricter nature conservation policies including restrictions of access to ecologically sensitive areas. The respondents indicated a willingness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…For example, [25] found that income and education affect tourists decision to visit the Kenting Coral Reef area in Taiwan; [26] showed that that gender, income, level of education and first-time visit affect visitors' preferences towards biodiversity conservation in the Yankari game reserve in Nigeria; and [27] found that older visitors were willing to pay more to support conservation of seamounts at the Galapagos Marine Reserve in Ecuador compared to younger ones, although gender was found to have a non-significant effect. In a study focusing on nature conservation programs in the Austrian Alps, [28], highlighted how visitors preferences are affected by income and family size. In [29], it was found that age, place of residence, education, income and number of past visits affected the recreational behavior of visitors to Wielkopolski National Park in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…For example, [25] found that income and education affect tourists decision to visit the Kenting Coral Reef area in Taiwan; [26] showed that that gender, income, level of education and first-time visit affect visitors' preferences towards biodiversity conservation in the Yankari game reserve in Nigeria; and [27] found that older visitors were willing to pay more to support conservation of seamounts at the Galapagos Marine Reserve in Ecuador compared to younger ones, although gender was found to have a non-significant effect. In a study focusing on nature conservation programs in the Austrian Alps, [28], highlighted how visitors preferences are affected by income and family size. In [29], it was found that age, place of residence, education, income and number of past visits affected the recreational behavior of visitors to Wielkopolski National Park in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…The database includes data on all plots of land managed by the ÖBf. Schirpke et al [54] also use this concept to assess the role of landscapes for outdoor recreation (see also [55]). In other words, the current management secures an increase of naturalness and biodiversity conservation at the cost of lumbering timber.…”
Section: Share Of Landmentioning
confidence: 99%
“…The HUGG Administrative Committee could properly develop tourism resources, control the number of visiting tourists in the peak season, and regulate tourist behavior to protect the HUGG ecosystem. A previous study indicated that the development of tourism resources is a double-edged sword [82]. If the HUGG Administrative Committee adopts the appropriate management measures, natural resource conservation and sustainable development can be achieved.…”
Section: Implications and Uncertaintiesmentioning
confidence: 99%